FACTORS CAUSING DISPUTE IN CONSTRUCTION INDUSTRY: CONTRACTORS’ PERSPECTIVES - Goh, Kelvin Zhen Hao; Wong, Shi Yee; Low, Wai Wah (Journal of Surveying, Construction and Property, 2023)
Construction dispute contributing to the involvement of billions US dollars in lawsuits and Asia was reported as the continent that had the highest dollars involved. Sarawak, the largest state in Malaysia, faced similar issues and such dispute had been reported in leading to cost and time overrun on the multiple large-scale construction projects. This research investigates factors causing dispute within Sarawak construction industry, by targeting G7 contractors, who has no limitation in handling the scale of project, by using simple random sampling method. Eighty-six contractors responded to the online questionnaire, amounting to 34% valid response rate. Descriptive statistics and Mann-Whitney U-test were used to investigate the viewpoint of respondents. The findings revealed that delay issue as the key cause of dispute to the contractors in Sarawak. Mann-Whitney U-test showed statistical significant differences on the perspectives of contractors between less than or equal to 10 years working experiences and more than 10 years experiences on four causes: poor cost management, finance issue, delay issue and different interpretation of contract provisions. This research could serve as a guideline for the contractors in handling dispute to improve construction companies’ profit margin and construction projects’ efficiency.